Inside Cover: Electrocatalytic and Solar‐Driven CO2 Reduction to CO with a Molecular Manganese Catalyst Immobilized on Mesoporous TiO2 (Angew. Chem. Int. Ed. 26/2016). Issue 26 (4th May 2016) - Rosser, Timothy E.; Windle, Christopher D.; Reisner, Erwin
Abstract : One small step for Mn A manganese catalyst immobilized on TiO2 gave a new benchmark turnover number as described by E. Reisner and co‐workers in their Communication onpage 7388 ff. The heterogenized catalyst operates at a low overpotential, which is the result of dimerization on the electrode surface. The molecular hybrid cathode was used in a photoelectrochemical cell enabling solar‐driven CO production by a photo‐unstable Mn catalyst for the first time.